2022
DOI: 10.1063/5.0131756
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-dependent contact angle hysteresis in electrowetting

Abstract: Contact angle hysteresis determines the stickiness of liquid on surfaces. Yet the adjustment of contact angle hysteresis remains highly challenging and extremely work-intensive. Here, we reveal a quadratic growth of contact angle hysteresis upon strengthening the inhomogeneous electric field in electrowetting under both direct and alternating current supplies. The anomalous evolution of contact angles under alternating current supplies is quantitatively interpreted by the oscillation of electrowetting forces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Thus, fully ionized PAA solutions exhibited an ∼50% increase in electrowetting hysteresis over weakly ionized PAA solutions. In a number of studies, it has been found that the electrowetting hysteresis is primarily caused by the roughness of the substrate surface and chemical heterogeneity. Notably, the dielectric surfaces in our experiments for PAA at low and high pHs had identical chemical properties and physical roughness. Therefore, it is reasonable to conclude that the PE ionization level affects the electrowetting hysteresis.…”
Section: Resultsmentioning
confidence: 58%
“…Thus, fully ionized PAA solutions exhibited an ∼50% increase in electrowetting hysteresis over weakly ionized PAA solutions. In a number of studies, it has been found that the electrowetting hysteresis is primarily caused by the roughness of the substrate surface and chemical heterogeneity. Notably, the dielectric surfaces in our experiments for PAA at low and high pHs had identical chemical properties and physical roughness. Therefore, it is reasonable to conclude that the PE ionization level affects the electrowetting hysteresis.…”
Section: Resultsmentioning
confidence: 58%